AB1023 PHYSICAL ACTIVITY LEVEL IN PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITISIN THE GERMAN NATIONAL PAEDIATRIC RHEUMATOLOGIC DATABASE: A COMPARISON WITH THE GENERAL POPULATION. (June 2019) - Milatz, Florian; Niewerth, Martina; Hörstermann, Jana; Geisemeyer, Nils; Haas, Peter; Horneff, Gerd; Kallinich, Tilmann; Hartmann, Matthias; Peitz, Joachim; Merker, Josephine; Minden, Kirsten
Abstract : Background: Insights in pathogenesis and the availability of new biologic drugs have created requirements and an increasing interest for encouragement of physical activity (PA) as long-term treatment option in patients with juvenile idiopathic arthritis (JIA). A low level of PA in healthy individuals is related to a higher incidence of overweight and hypertension in later life. This low level of PA might even be more dangerous for children with JIA, as they also have elevated inflammatory parameters, perhaps increasing the risk of future cardiovascular diseases. Objectives: Since children and adolescents with physical disabilities may have an increased risk for developing a sedentary lifestyle, the objective was to investigate if encouragement of PA in most German medical care settings has led to PA levels in JIA similar to that of healthy counterparts. Methods: Data from children and adolescents with JIA recorded in the German National Paediatric Rheumatologic Database (NPRD) in the year 2017 were considered for the analyses. In accordance with the methodology used in the general population survey [1], the achievement of the WHO recommendations on PA for health was determined on the basis of self-reported outcomes in individuals aged 3 to 17 years. Patients met the WHO criteria if they stated to be physically active for at least 60 minutes per day. Results: In 2017, the data from 5.918 patients (mean age 11.2 ± 4.1 years, female 67%, disease duration 4.6 ± 3.7 years, persistent oligoarthritis 42%) were available for evaluation. Almost 35% of patients aged 3 to 17 years met the recommended physical activity level (72% aged 3 to 6; 47% aged 7 to 10; 27% aged 11 to 13; 16% aged 14 to 17). In the general population, 26% fulfilled the WHO recommendations on PA (46% aged 3 to 6; 27% aged 7 to 10; 38% aged 11 to 13; 12% aged 14 to 17). In multivariable analyses, increasing age (OR 1.27; 95%CI: 1.24-1.29), psoriatic arthritis (OR 1.49; 95%CI: 1.06-2.11), overweight (OR 1.33; 95%CI: 1.04-1.71), functional disability (OR 0.83; 95%CI: 0.69-0.98), and worse patient-reported overall well-being (OR 1.10; 95%CI: 1.03-1.17) were associated with non-achieving the recommended PA amount. Conclusion: Encouraging PA in most German medical care settings and the growing attention of the importance of regular PA for pleasure and health benefits may have led to a similar or even higher amount of PA compared to healthy counterparts. However, since a large proportion does not meet the global recommendations on PA, further research should address especially patients with inactive or minimal active disease who have previously largely refrained from PA. In order to derive adequate strategies, future work is warranted to comprehensively and objectively measure PA behavior in this population. References: [1] Finger JD, et al. Körperliche Aktivität von Kindern und Jugendlichen in Deutschland - Querschnittergebnisse aus KiGGS Welle 2 und Trends. Journal of Health Monitoring 2018;3:24–31. Acknowledgement: The National Paediatric Rheumatological Database has been funded by the German Children Arthritis Foundation (Deutsche Kinder-Rheumastiftung), AbbVie, Pfizer and Chugai. Disclosure of Interests: Florian Milatz: None declared, Martina Niewerth: None declared, Jana Hörstermann: None declared, Nils Geisemeyer: None declared, Peter Haas Grant/research support from: Pfizer, Gerd Horneff: None declared, Tilmann Kallinich Grant/research support from: Novartis, Speakers bureau: Sobi, Roche, Novartis, CLB, Matthias Hartmann: None declared, Joachim Peitz: None declared, Josephine Merker: None declared, Kirsten Minden Consultant for: AbbVie